Resonant Scattering of Plane‐Wave and Twisted Photons at the Gamma Factory. Issue 3 (16th September 2021) - Serbo, Valeriy G.; Surzhykov, Andrey; Volotka, Andrey
Abstract: A theoretical investigation of the resonant elastic scattering of laser photons by ultra‐relativistic partially stripped ions, that is the core process of the Gamma Factory project, is presented. Special emphasis in the study is placed on the angular distribution and polarization of scattered photons as observed in the collider and ion‐rest reference frames. In order to describe these (angular and polarization) properties for arbitrary relativistic many‐electron ion, the general approach, based on the application of irreducible polarization tensors, is laid down. By making use of the polarization tensors, the scattering of both conventional plane‐wave‐ and twisted (or vortex) photons is explored in detail. For the former case, it is shown how the propagation directions and polarization states of incident and outgoing photons are related to each other for the n S 0 → n ′ P 1 → n S 0 n S_0 → n^′ P_1 → n S_0, n S 1 / 2 → n ′ P 1 / 2 → n S 1 / 2 n S_1/2 → n^′ P_1/2 → n S_1/2, and n S 1 / 2 → n ′ P 3 / 2 → n S 1 / 2 n S_1/2 → n^′ P_3/2 → n S_1/2 resonant transitions. For the scattering of initially twisted light that carries non‐zero orbital angular momentum, the angular distribution of secondary photons is explored and the conditions under which they are also twisted are discussed. Abstract : The paper reports the theoretical study of the resonant photon scattering by partially stripped ions. For this—key for the Gamma Factory—process, the angular and polarization properties of scattered radiation are mainly studied. An efficient theoretical toolbox is presented for the investigation of these (angular and polarization) properties for any setup of future Gamma Factory experiments.